The old Hebrew particle gam : a syntactic-semantic description of gam in Gn-2Kg - Van der Merwe, Christo H. J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- University of Stellenbosch, 1988.